A Computational Study of Inlet Turbulence on Delta Wing Flow - Tran, Ngoc Khanh; Hoang, Thi Kim Dung; Nguyen, Phu Khanh (Old Journal, 2017)
Effect of turbulence flow to dynamic characteristic of high sweep-back angle Delta wing was performed in subsonic flow. Numerical method (SIM), based on CFD methods using ANSYS/FLUENT software, was carried out to study this phenomenon. At low Reynolds number, air velocity 2.5m/s, Delta wing was investigated with a range of attack angle from 0 to 40° within three cases of turbulent intensity, which varied from 0.5% to 15% due to parameter of square grid. Decay of turbulence intensity with and without grid was considered. Change of dynamic characteristic of Delta wing caused by different change of turbulence intensity at inlet flow was also observed. Finally, interaction between turbulent flow and vortex on upper wing was clarified.